Early Urinary Biomarkers in Pediatric Autosomal Dominant Polycystic Kidney Disease (ADPKD): No Evidence in the Interest of Urinary Neutrophil Gelatinase-Associated Lipocalin (uNGAL) - Tsingos, Marianthi; Merlini, Laura; Solcà, Marco; Goischke, Alexandra; Wilhelm-Bals, Alexandra; Parvex, Paloma (Frontiers in Pediatrics, 2019)
Background: Autosomal Dominant Polycystic Kidney Disease (ADPKD) is increasingly diagnosed during childhood by the presence of renal cysts in patients with a positive familial history. No curative treatment is available and early detection and diagnosis confronts pediatricians with the lack of early markers to decide whether a nephroprotective treatment should be introduced and prevent the progression of renal failure. Neutrophil Gelatinase-Associated Lipocalin (NGAL) is a tubular protein that has been recently proposed as an early biomarker of renal impairment in the ADPKD adult population. Methods: Urinary NGAL (uNGAL) levels were measured in 15 ADPKD children and compared with 15 age and gender matched controls using parametric, non-parametric and Bayesian statistics. We also tested the association of uNGAL levels with markers of disease progression, such as proteinuria, albuminuria, blood pressure and Total Kidney Volume (TKV) using correlation analysis. Results: No difference in mean uNGAL levels was observed between groups (ADPKD: 26.36 ng/ml; Controls: 27.24 ng/ml; P=.96). Moreover, no correlation was found between uNGAL and proteinuria (P=.51), albuminuria (P=.69), TKV (P=.68) or mean arterial pressure (P=.90). By contrast, TKV was positively correlated with proteinuria (P=.04), albuminuria (P=.001) and mean arterial pressure (P=.03). Conclusion: uNGAL did not confirm its superiority as a marker of disease progression in a pediatric ADPKD population. In the contrary, TKV appears to be an easy measurable variable and may be promising as a surrogate marker to follow ADPKD progression in children.